Intolerance of uncertainty, digital stress, emotion dysregulation: undermining psychological maturity in early adolescents - Eryilmaz, Ali; Kocyigit, Busra; Huebner, E. Scott (SPRINGER, 2026)
The purpose of this research was to evaluate the mediating roles of digital stress and emotional dysregulation in the link between intolerance of uncertainty and early adolescents' psychological maturity within the context of a psychoanalytic framework. A total of 408 Turkish public-school students participated (Age range = 10-15, mean age = 12.97, standard deviation of age = 0.96). Among the students, there were 197 girls (48%) and 211 boys (52%). The students completed measures of intolerance of uncertainty, digital stress and emotional dysregulation, and psychological maturity. Data were analyzed using a two-stage structural analysis. The measurement model was first validated, and then structural equation modelling analysis was conducted. To estimate direct, indirect, and total effects, a bootstrap analysis with 5000 resamples and 95% bias-corrected confidence interval (CI) was used. Structural equation modeling demonstrated a significant mediating role of digital stress and emotional dysregulation in the relationship between intolerance of uncertainty and psychological maturity. Intervention programs aimed at enhancing adolescents' psychological maturity should incorporate strategies for coping with uncertainty, reducing digital stress, and developing emotional regulation skills.
Keywords: Adolescence; Psychological maturity; Intolerance of uncertainty; Digital stress; Emotional dysregulation; ANXIETY; DIFFICULTIES; ASSOCIATIONS; SYMPTOMS; VERSION; Psychology